Exploring Student’s Ability in Applying Writing Mechanism in Recount Text - Purba, onda (INTERACTION: Jurnal Pendidikan Bahasa, 2018)
This study is carried out with the purposed that after gives the test by recount text. The students are hoped can be able to increase their ability in applying writing mechanism. This study is non-experimental research. Non-experimental is used as the mean in collecting the data. The population of this study was the students at the Third Grade of MAN Model Sorong in the years 2014/2015, by the number were 180 students. The sample of this study was the students of XII IPA I by the number were 23 students. The writer used only one test and non-experimental design in this study. The result of study was presented into tables and had explained by percentage. In analysing data, the writer used table of category and score range in writing based on Sahidu. The result of this study showed that there were 11 students in excellent category (47,8%), 7 students in good category (30,4%), 4 students in average category (17.3%) and the last in poor category 1 student (4,34%). The mean from 23 students, there are 11 students almost writing perfectly in using the 6 elements in punctuation and capital letters. The writer concluded that ability of the students in XII IPA I in MAN MODEL Sorong was used capital letters and punctuation good enough.